GREENPEG Tysfjord test site data April 2021 - Brönner, Marco; Larsen, Bjørn Eskil; Haase, Claudia (Zenodo, 2021)
ArcGis Pro GIS database containing geological, geophysical and geochemical data for the GREENPEG Tysfjord test site, Norway